Inhibition of IL-10 and TGF-β receptors on dendritic cells enhances activation of effector T-cells to kill cholangiocarcinoma cells - Chutamas Thepmalee (2018)
© 2018 Siriraj Hospital, Mahidol University Tumor escapes host immune responses by producing immunosuppressive cytokines, such as IL-10 and TGF-β, secreted into the tumor microenvironment. These cytokines play important roles in the suppression of dendritic cell (DC) function, leading to decreased immune responses of the effector CD4 + and CD8 + T cells. To improve DC functions and enhance cytolytic activity of activated effector T-cells, we suppressed the effect of these cytokines on DCs by using specific neutralizing antibodies that inhibit IL-10 and TGF-β receptors. Monocyte-derived DCs generated in vitro showed up-regulation of MHC (HLA-DR) and co-stimulatory molecules (CD40 and CD86). The IL-10 and TGF-β receptors were expressed and localized on cell membrane of DCs, as shown by Western blot analysis and immunofluorescence staining, whereas the IL-10 and TGF-β ligands were detected in the culture supernatants of DCs and cholangiocarcinoma (CCA) cell line, respectively. Inhibition of the IL-10 and TGF-β receptors on DCs by specific neutralizing antibodies significantly increased level of IFN-γ and enhanced cytolytic activity of the DC-activated effector T-cells against CCA cell line. These results indicate that the IL-10 and TGF-β receptors are the targets for inhibition to increase DC functions and enhance cytolytic activity of the DC-activated effector T-cells against CCA cells. Thus, inhibition of the IL-10 and TGF-β receptors on DCs is crucial in the preparation of DC-activated effector T cells for adoptive T-cell therapy.